Perbandingan Kapasitas Inflitrasi Antara Tanah Terkelola Secara Organik Dan Konvesional - Zai, Putra; Zebua, Andi Donal Putra (CV. SINAR HOWUHOWU, 2024)
This research aims to explore the effect of soil density on plant root performance in various climatic conditions. Experiments were carried out by comparing plant root growth at high (1.5 g/cm³) and low (1.2 g/cm³) soil density in locations representing tropical, dry and temperate climates. Results showed that high soil density significantly inhibited root growth, with average root length reaching 30 cm at low density and only 15 cm at high density. In addition, the ability to absorb water and nutrient content in roots is also higher in low density soil treatment. These findings confirm that maintaining soil density at optimal levels is important to support healthy root growth and plant productivity. The research also found that climate conditions influenced the relationship between soil density and root performance, with plants in dry climate locations experiencing greater impacts from high soil density. Recommendations for sustainable soil management practices are suggested to improve root health and agricultural productivity.